Türkiye’s Economic Trilemma: Inflation, Inequality, and Growth - Özdurak, Caner; Çipe, Bilge (International Journal of Economics and Financial Issues, 2025)
This study investigates the intricate relationship between inflation, income inequality, and economic growth in Türkiye. Recent unconventional monetary policies, particularly artificial interest rate cuts, have exacerbated existing economic disparities, disproportionately benefiting affluent individuals. This has contributed to rising income inequality and consumption-driven inflationary pressures. The research explores the impact of tighter monetary policies and increased interest rates on the behavior of wealthy individuals and their influence on inflation persistence. Additionally, the study delves into the disproportionate burden of services inflation on lower-income households. Addressing this issue requires a multifaceted approach, including policies to enhance the affordability of essential services, strengthen the social safety net, and promote inclusive economic growth. By examining these interconnected factors, the study aims to shed light on the underlying dynamics driving inflation, income inequality, and economic growth in Türkiye. The objective is to develop a comprehensive policy framework that addresses the root causes of these issues and fosters sustainable economic development for all segments of society.